EVENT-DRIVEN ARCHITECTURES IN INTEGRATION AS A SERVICE: A TECHNICAL DEEP DIVE - Kapil Pothakanoori, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This article explores the transformative role of Event-driven Architecture (EDA) in modern integration-as-a-service platforms. As organizations increasingly adopt cloud computing and distributed systems, EDA has emerged as a crucial paradigm for building scalable and responsive integration solutions. The article examines various aspects of EDA implementation, including technical foundations, architectural patterns, implementation considerations, error handling, performance optimization, security frameworks, and monitoring strategies. Through comprehensive analysis of enterprise deployments, the study demonstrates how EDA enables organizations to achieve improved system responsiveness, reduced infrastructure costs, and enhanced operational efficiency. The article provides insights into how event sourcing, CQRS patterns, message queue designs, and other architectural components contribute to building robust distributed systems. Additionally, it explores the critical aspects of security, error handling, and observability in EDA implementations, offering practical guidance for organizations transitioning to event-driven integration platforms.